Strengthened Common Security and Regional Interdependence in European Union: From Brexit to Covid-19 Pandemic (Department of International Relations, Universitas Brawijaya, 2022)
The results of Brexit referendum have led to a differentiation in terms of decisions and responds between leaders in the European Union about the future of this regional organization. As a result, the European Union was divided into two groups which is “more Europe” and “less Europe” as it hinders in reaching consensus regarding the formulations of a policy in the European Union. This research uses the theory of Interdependence and common security to analyze European Union’s responds to Brexit and COVID-19 where the compilation of the analysis’ results was carried out using qualitative methods and an explanatory approach. In fact, the COVID-19 Pandemic brought a negative impact in many fields that can destabilize not only member countries, but also regional security in Europe. The results of this research indicate that the European Union, which was heading towards disintegration due to Brexit, was able to set aside fragmented national interests by increasing interdependence to achieve common security in the European Union due to the COVID-19 Pandemic. This interdependence is proven by holding meetings and a common viewpoint on the threat of Covid-19, so that policy formulation can be carried out comprehensively and responsively.